Trabalhador rural, quilombola e a representação de categorias jurídicas: o conflito em Alcântara e a tutela dos direitos coletivos - Rocha, Kelda Sofia da Costa Santos Caires (2022)
The scope of this dissertation is to analyze the production of documents in the judicial sphere by both state and social agents, examining the legal categories rural worker, quilombola in relation to the representation of legal categories from the conflict in Alcântara and the protection of rights collectives, this raising the discussion of the process of legitimizing the changes of legal categories in face of the demand of the quilombola communities of Alcântara in the face of the state. I focused the analysis on court documents, as will be explained, due to the need to delimit the focus of the study, already realizing the type of practical result that had been obtained throughout the development of the research. Therefore, based on the analysis of the conflict between the quilombola communities of Alcântara and the State, as an emblematic case, I propose to discuss, based on the identified legal experience, the construction of collective law, because despite the constant conflicts inside and outside the courts, this was translated in a new interpretation of the Federal Constitution of 1988, based on expressive legal pluralism and, therefore, it is highlighted that the research seeks to address the relationship between the change of the category "rural worker" linked to the category "squatter", as it appears in the documents produced within the legal proceedings, used to designate those expropriated during the beginning of the implementation of the Alcântara Launch Center (CLA), for the ethnic category "quilombola", from the idea of building the protection of collective rights, with the perception how this change was incorporated in the legal world and in the documents prepared, based on the need to break with the law. state logic that permeates the construction of the standard. The methodology adopted involves the inductive method, based on the use of ethnography of documents, according to an analysis involving public court documents, some of which were easily accessible and others required special authorization to access them.